DNA CPR SCOTLAND POLICY: AN AUDIT OF THE SUCCESS OF IMPLEMENTATION IN NHS TAYSIDE. Issue Volume 4: Issue (2014)Supplement 1 (1st March 2014) - Douglas, Claire; Harrison, Michelle; Todd, Ann-Marie; Munro, Jemma; Essex, Jane; Karuny, Bheena
Abstract : Introduction: People who have advanced metastatic cancer or a poor performance status are unlikely to survive a cardiac arrest. In May 2010, the Scottish Government published the National DNACPR Integrated Adult policy with the aim of reducing unsuccessful attempts at resuscitation by improving decision making and communication about DNACPR decisions. Our study aimed to assess the success of policy implementation in NHS Tayside. Methods: A prospective casenote audit was performed for all patients admitted within a 30 day period to four clinical areas in Tayside; oncology, cardiology, MFE (medicine for the elderly) and Cornhill Macmillan Centre (hospice). Information obtained included diagnosis, past medical history, performance status, presence of a DNACPR form, patient outcome and whether completion and transfer of the form adhered to policy guidance. Results: 18% (5/27) of patients in Cornhill and 23% (7/30) of patients in oncology were admitted with a DNACPR form but none to cardiology (0/52) or MFE (0/24). During admission forms were present or completed in 92% (25/27) of patients from Cornhill, 78% (23/30) from oncology, 19% (10/52) from cardiology and 29% (7/24) from MFE respectively. A significant proportion of patients without a form had metastatic cancer or poor performance status. Of patients discharged or transferred, the DNACPR form went with the patient in 100% of patients from Cornhill, 4% from oncology but none from cardiology or MFE. The form was either left in the notes, sent to the GP or the decision was reversed on discharge. Conclusion: DNA CPR forms are being completed appropriately for many patients in the acute setting in Tayside, however many patients are not sent home with the forms despite the chances of surviving a cardiac arrest being negligible. Improvement in decision making and communication of DNACPR decisions with the patient, family and other professionals is required.